Countering Islamophobia through webcomics on Instagram - Dwimay, Fawzy; A.Manaf, Aini Maznina; Tengku Azzman, Tengku Siti Aisha (IIUM Press, 2022)
The widespread use of social media is directly proportional to the widespread practice of spreading Islamophobia in the digital realm, especially in Western societies whose understanding of Islam or Muslims is primarily based on negative media stereotypes. Various efforts were made, including from Muslim groups to counter against these negative stereotypes through social media and form a counter-narrative. One of them is the Instagram account @yesimhotinthis, which conveys a message countering Islamophobia from an Egyptian-American Muslim’s perspective through the format of autobiographical webcomics. The approach taken is different from mainstream comics, which are mostly superhero themed. This study analyzes how countering Islamophobia is represented and how Instagram is used to counter Islamophobia. A qualitative analysis of seven webcomics of @yesimhotinthis was conducted. Results indicated that representation of countering Islamophobia emphasized more on the aspect of equality and highlighting similarities between Muslims and non-Muslims in social aspects. In addition, Instagram is utilized by adjusting the relations between webcomicsand its captions, giving the impression that although Islamophobia is countered in a casual way, it is still a serious problem